Removal of nitrogen and phosphorus from reject water of municipal wastewater treatment plant - Guo, Chenghong (2011)
Reject water, the liquid fraction produced after dewatering of anaerobically digested activated sludge on a municipal wastewater treatment plant (MWWTP), contains from 750 to 1500 mg N /L of ammonium and up to 130 mg P/L phosphorus. It contributes from 10 to 30% of the nitrogen load and from 10% to 80% of phosphorus load on the main stream of MWWTPs. The removal of phosphorus and nitrogen from reject water could significantly reduce the nutrient load to the main stream of the MWWTP and improve the effluent quality.